2015
DOI: 10.1159/000374115
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A Promotes Arginase-1 Production and 2,4-Dinitrochlorobenzene-Induced Acute Hyperinflammation in Human Papillomavirus E7 Oncoprotein-Expressing Skin

Abstract: Human papillomaviruses (HPVs) have evoked numerous mechanisms to subvert host innate immunity and establish a local immunosuppressive environment to facilitate persistent virus infection. Topical application of 2,4-dinitrochlorobenzene (DNCB) was speculated to overcome this immunosuppressive environment and was employed in the immunotherapy of HPV-associated lesions. We have previously shown that DNCB treatment of skin expressing HPV16.E7 protein, the major oncogenic protein expressed in HPV-associated premali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…Secondly, in 4 patients, we found heterogeneity: MDSCs of some patients employed IL-17 and arginase I. In these cases, IL-17 may upregulate arginase I expression in MDSCs (He et al , 2010; Tran le et al , 2015). By contrast, MDSCs from other patients employed the IFN-γ/iNOS axis (Faure et al , 1999).…”
Section: Discussionmentioning
confidence: 84%
“…Secondly, in 4 patients, we found heterogeneity: MDSCs of some patients employed IL-17 and arginase I. In these cases, IL-17 may upregulate arginase I expression in MDSCs (He et al , 2010; Tran le et al , 2015). By contrast, MDSCs from other patients employed the IFN-γ/iNOS axis (Faure et al , 1999).…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, IL-17KO C57BL/6 mice expressed lower levels of mRNA coding for molecules associated with M2 activity, including arginase 1 (54). Another study showed that IL-17A induces arginase 1 production in a model of human Papillomavirus (55). In this case, arginase 1 would be active in M2-macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…E7 interaction with Rb protein is necessary to attract T cells to E7 transgenic skin K14.E7 transgenic mouse skin exhibits an immune cell infiltrate and regulatory cytokine production (Chandra et al, 2016;Choyce et al, 2013;Gosmann et al, 2014a;Gosmann et al, 2014b;Mattarollo et al, 2010b;Tran le et al, 2015). To determine whether the lymphocytic infiltrate observed in E7 transgenic skin requires interaction of E7 with Rb protein, we utilized a double transgenic mouse model expressing HPV16 E7 and a mutant Rb (K14.E7xRb L/L ) that fails to bind E7 and therefore lacks epithelial hyperplasia without perturbing other Rb functions (Balsitis et al, 2005;Dick et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Arg-1 production is independent of T and B lymphocytes, as evidenced by no significant difference in Arg-1 expression between K14.E7 and K14.E7xRag -/mice, where no T cells and B cells exist in the latter (Tran et al, 2014). Depletion of IL-17 abolished DNCB-induced Arg-1 production and hyper-inflammation, indicating that IL-17 is the key inducer of Arg-1 (Tran le et al, 2015). Taken together, local determinants, such as IL-1β, Arg-1 and IL-17, control the outcome of K14.E7 skin grafts and inflammatory response towards topical immune therapies.…”
Section: K14e7xrb δL/δl As E7-expressing Non-hyperplastic Modelmentioning
confidence: 92%
See 1 more Smart Citation